Kearifan Lokal Dalam Teks Berita Lelayu di Lingkungan Etnik Jawa - Sudiyana, Benedictus; Marmoah, Sri; Nurhasanah, Farida; Wicaksana, Muhlis Fajar (Jurnal Ilmiah Dikdaya, 2023)
The news text that grew up among Javanese ethnicity highlighted a lot of local wisdom, one of which was religious value. This study aims to describe the practice of local wisdom in Javanese lelayu news texts in the Yogya-Surakarta community. The research method is carried out with qualitative descriptive of text objects. Data in the form of words, language expressions, phrases, clauses, and sentences, which contain positive value messages as expressions and representations of mikul dhuwur mendhem jero in withered news texts. Data collection is carried out by recording text based on criteria of data characteristics. Data analysis was carried out by utilizing the fields of linguistic semantics, language variety, pragmatics, and representation of social actors, with identification, classification, and interpretation procedures as qualitative research steps. The results showed that the disclosure of the value of "mikul dhuwur" was used (a) small names, (b) kinship greetings, (c) titles/titles, (d) religious names, (e) real names, (f) verse quotations, (g) deiksis persona respectfully, (i) care for speech partners, (j) lists of relatives as a representation of family harmony; The expression "mendhem jero" is used (a) a subtle term/euphemism for the event of death, (b) the smoothing of the event of the cause of death, (c) the circumstances/atmosphere at the time of death, (d) asking for forgiveness, (e) asking for settlement of receivables, and (f) asking for prayers for the deceased.